2020
DOI: 10.1186/s13643-020-01343-4
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese herbal medicine for treating novel coronavirus (COVID-19) pneumonia: protocol for a systematic review and meta-analysis

Abstract: Background: A new type of coronavirus, novel coronavirus , is causing an increasing number of cases of pneumonia and was declared a Public Health Emergency of International Concern by the World Health Organization on 30 January 2020. The virus first appeared in Wuhan, China, in late December 2019, and traditional Chinese herbal medicine is being used for its treatment. This systematic review and meta-analysis will assess studies of the effects of traditional Chinese herbal medicine in COVID-19 pneumonia.Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(59 citation statements)
references
References 23 publications
1
57
0
Order By: Relevance
“…Many researchers have reported the beneficial effect of natural compounds in treating HIV infections (Reiter et al, 2015;Salehiet al, 2018) Hydroxychloroquine was also observed to significantly decrease SARS-CoV-2 infection (Gautretet al, 2020). Li et al, 2020 reported that traditional Chinese herbal medicine treatments alone or in combination with western medicine can be successful in preventing and treating COVIS-19 (Li et al, 2020). Based on these reports it is clear that it is necessary to repurpose natural compounds especially phytochemicals as prophylaxis to manage patients with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have reported the beneficial effect of natural compounds in treating HIV infections (Reiter et al, 2015;Salehiet al, 2018) Hydroxychloroquine was also observed to significantly decrease SARS-CoV-2 infection (Gautretet al, 2020). Li et al, 2020 reported that traditional Chinese herbal medicine treatments alone or in combination with western medicine can be successful in preventing and treating COVIS-19 (Li et al, 2020). Based on these reports it is clear that it is necessary to repurpose natural compounds especially phytochemicals as prophylaxis to manage patients with COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is not surprising that thousands of TCM practitioners across China have been working along with regular medical doctors to control the COVID-19 disease. The clinical data generated from tens of thousands of confirmed cases are being subjected to meta-analyses to ascertain their actual effectiveness (Li et al, 2020). In the meantime, the Diagnosis and Treatment Protocol of COVID-19 by the National Health Commission has already advised to integrate TCM in the treatment of COVID-19 patients to effectively relieve symptoms such as fever, cough, sore throat, myalgia, and fatigue, shorten the course of the disease, reduce the probability of life-threatening complications (Xu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on clinical results, the General Office of the National Health, and the Office of the State Administration of Traditional Chinese Medicine encouraged the integration of herbal TCM and Western medicine in the treatment of respiratory complications in Coronavirus infections with different prescriptions recommended in different stages of disease (Leung, 2007). After SARS-CoV-2 disease outbreak, a number of clinical trials with Traditional Herbal Medicines (THM) have been added to the body of evidence with some favorable findings when compared to standard antiviral therapy (Langeder et al, 2020;Li et al, 2020;Luo et al, 2020;Rastogi et al, 2020).…”
Section: Plectranthus Amboinicus Lour -Lamiaceae (Leaves)mentioning
confidence: 99%
“…Makino], Forsythia Fruit [Forsythia suspensa (Thunb.) Vahl], and Bitter Apricot Seed (Prunus armeniaca L.) are the most frequently prescribed herbs (Li et al, 2020). Their meta-analysis showed that herbal medicines are effective in halting the disease progression from mild to critical, decreasing hospitalization rate, shortening time of hospital stay, as well as alleviating COVID-19 associated symptoms like fever, cough, fatigue, and inflammation (Li et al, 2020).…”
Section: Herbal Medicines Alleviating Acute Respiratory Infectionmentioning
confidence: 99%